On Adjusting the HP-Filter for the Frequency of Observations - Morten O. Ravn; Harald Uhlig (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper studies how the HP-Filter should be adjusted, when changing the frequency of observations. It complements the results of Baxter and King (1999) with an analytical analysis, demonstrating that the filter parameter should be adjusted by multiplying it with the fourth power of the observations frequency ratios. This yields an HP parameter value of 6.25 for annual data given a value of 1600 for quarterly data. The relevance of the suggestion is illustrated empirically.
Keywords: 330